Matrix Metalloproteinase‐1 Expression in Women With and Without Pelvic Organ Prolapse: A Systematic Review and Meta‐analysis - Feng, Y (Clin Transl Sci, 2016)
This meta‐analysis was conducted to estimate the association between matrix metalloproteinase‐1 (MMP‐1) expression and pelvic organ prolapse (POP) in women. Relevant studies published before 6 December 2015 were identified by searching PubMed, Ovid, EBSCO, and EMBASE. A total number of five case–control studies, including 182 POP cases and 192 controls, were identified. The results indicated that women without POP had a lower MMP‐1 level of expression compared with women with POP (odds ratio = 0.54, 95% confidence interval: 0.43–0.67, P = 0.000). After stratification by biopsy site, ethnicity, or menopausal status, this finding was also confirmed in the subgroup analysis with no significant changes. Egger's linear regression test revealed a potential publication bias (P = 0.028). The findings of our study indicate that women who suffer from POP have a higher expression level of MMP‐1 than women without POP.